A biomechanical analysis of anterior cervical discectomy and fusion alone or combined cervical fixations in treating compression-extension injury with unilateral facet joint fracture: a finite element study - Chen Jin (BMC, 2021)
Abstract Background Compression-extension injury with unilateral facet joint fracture is one of the most devastating injuries of subaxial cervical spine. However, it is not yet clear which fixation technique represents the optimal choice in surgical management. This study aims to assess the construct stability at the operative level (C4/C5 cervical spine) following anterior cervical discectomy and fusion (ACDF) alone and combined fixation techniques (posterior-anterior fixations). Methods A previously validated three-dimensional C2-T1 finite element model were modified to simulate surgical procedures via the anterior-only approach (ACDF) and combined cervical approach [(transarticular screw, lateral mass screw, unilateral pedicle screw, bilateral pedicle screw) + ACDF, respectively] for treating compression-extension injury with unilateral facet joint fracture at C4/C5 level. Construct stability (range of rotation, axial compression displacement and anterior shear displacement) at the operative level was comparatively analyzed. Results In comparison with combined fixation techniques, a wider range of motion and a higher maximum von Mises stress was found in single ACDF. There was no obvious difference in range of motion among transarticular screw and other posterior fixations in the presence of anterior fixation. In addition, the screws inserted by transarticular screw technique had high stress concentration at the middle part of the screw but much less than 500 MPa under different conditions. Furthermore, the variability of von Mises stress in the transarticular screw fixation device was significantly lower than ACDF but no obvious difference compared with other posterior fixations. Conclusions Of the five fixation techniques, ACDF has proven poor stability and high structural stress. Compared with lateral and pedicle screw, transarticular screw technique was not worse biomechanically and less technically demanding to acquire in clinical practice. Therefore, our study suggested that combined fixation technique (transarticular screw + ACDF) would be a reasonable treatment option to acquire an immediate stabilization in the management of compression-extension injury with unilateral facet joint fracture. However, clinical aspects must also be regarded when choosing a reconstruction method for a specific patient.